2014
DOI: 10.1021/ac501085d
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Green Synthesis of High Quantum Yield Oxygen-Doped, Nitrogen-Rich, Photoluminescent Polymer Carbon Nanoribbons as an Effective Fluorescent Sensing Platform for Sensitive and Selective Detection of Silver(I) and Mercury(II) Ions

Abstract: This work reports on a facile, economical, and green preparative strategy toward water-soluble, fluorescent oxygen-doped, nitrogen-rich, photoluminescent polymer carbon nanoribbons (ONPCRs) with a quantum yield of approximately 25.61% by the hydrothermal process using uric acid as a carbon-nitrogen source for the first time. The as-prepared fluorescent ONPCRs showed paddy leaf-like structure with 80-160 nm length and highly efficient fluorescent quenching ability in the presence of mercury(II) (Hg(2+)) or silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 63 publications
3
94
0
Order By: Relevance
“…However the reaction between -SH and Hg 2+ were happened, the absorption peak of the -SH was obviously decreased. The peaks at 1239 and 1370 cm −1 were associated with the C-N stretching in the benzenoid and quinoid imine units, aromatic C=N heterocycles stretching vibrations are at1309−1650 cm −1 [41,42]. All the above observations indicate the successful formation of O-Cys including -SH.…”
Section: Characterization Of O-cysmentioning
confidence: 80%
See 1 more Smart Citation
“…However the reaction between -SH and Hg 2+ were happened, the absorption peak of the -SH was obviously decreased. The peaks at 1239 and 1370 cm −1 were associated with the C-N stretching in the benzenoid and quinoid imine units, aromatic C=N heterocycles stretching vibrations are at1309−1650 cm −1 [41,42]. All the above observations indicate the successful formation of O-Cys including -SH.…”
Section: Characterization Of O-cysmentioning
confidence: 80%
“…4a, red curve).The most probable explanation for the quenching of PL of O-Cys in the presence of Hg 2+ was based on the electron transfer mechanism. That is, Hg 2+ is an acid of borderline hardness (according to the hard and soft acids and bases principle) and had strong affinity for sulfur donor atoms than the nitrogen atom, as result of forming the stable metal complexes [42]. Morever, when adding a strong Hg 2+ chelator (such as EDTA), Hg 2+ were removed from the surface of O-Cys by forming metal chelates with EDTA, which resulted in the PL recovery of O-Cys (Fig.…”
Section: Detection Of Hg 2+mentioning
confidence: 99%
“…The three peaks at 284.6, 285.7 and 287.9 eV would respectively correspond to C-C/C=C, C-N and C=O bonds. 37,38 Two peaks shown in the N 1s spectrum (Fig. 3C) at the binding energy of 399.5 and 401.4 eV can be respectively attributed to C-N-C and N-H. 39 Furthermore, the proportion of C-N-C accounted for 91.37%.…”
Section: Resultsmentioning
confidence: 96%
“…The limit of detection (LOD) was estimated to be 23 nM (~5 ppb) at a signal-to-noise ratio of 3, which is lower than the maximum contamination level of Hg 2+ in drinking water permitted by the World Health Organization (WHO, 6 ppb). 33,34 The superior sensitivity is much better than those for previous reported probes (Tables S1 and S2, Supporting Information). All these observations indicated that the N-CDs fluorescent sensing probe exhibits very promising application toward Hg 2+ detection.…”
Section: +mentioning
confidence: 86%